2011
DOI: 10.1159/000331003
|View full text |Cite
|
Sign up to set email alerts
|

Welfare, Temperance and Compulsory Commitment to Care for Persons with Substance Misuse Problems: A Comparative Study of 38 European Countries

Abstract: Aims: The study explores the existence and types of law on compulsory commitment to care (CCC) of adult substance misusers in Europe and how such laws are related to variations in demographics, alcohol consumption and epidemiology in misuse of opiates, cocaine, amphetamines, temperance culture heritage, health and welfare expenditure, and involvement and role of the state in welfare distribution. Material and Methods: Legal information on laws on CCC of misusers was obtained primarily through a survey of 38 Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…With these added to compulsory civil commitment, Israelsson and Gerdner [4] concluded that 82% of the 90 countries had some law on CCC at the eve of the 20th century. In a more recent study on 38 European countries, Israelsson [5] found that 74% had some such law. Room [6] reports from 147 countries that 42.5% have law on ‘special legislation for the compulsory treatment of substance use disorder’, while 20.5% have drug courts, and 52.2% have programs on diversion to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…With these added to compulsory civil commitment, Israelsson and Gerdner [4] concluded that 82% of the 90 countries had some law on CCC at the eve of the 20th century. In a more recent study on 38 European countries, Israelsson [5] found that 74% had some such law. Room [6] reports from 147 countries that 42.5% have law on ‘special legislation for the compulsory treatment of substance use disorder’, while 20.5% have drug courts, and 52.2% have programs on diversion to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Porter et al [1] report on legislations up to 1982, while Israelsson [5] report on legislations up to 2009. Thus, there is a time span of at least 27 years between data collections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations